2020
DOI: 10.48550/arxiv.2009.02465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A spectral study of the black hole X-ray binary MAXI J1820+070 with AstroSat and NuSTAR

Sudip Chakraborty,
Nilam Navale,
Ajay Ratheesh
et al.

Abstract: MAXI J1820+070 is a newly discovered transient black hole X-ray binary, which showed several spectral and temporal features. In this work, we analyse the broadband X-ray spectra from all three simultaneously observing X-ray instruments onboard As-troSat, as well as contemporaneous X-ray spectra from NuSTAR, observed during the hard state of MAXI J1820+070 in March 2018. Implementing a combination of multicolour disc model, relativistic blurred reflection model relxilllpCp and a distant reflection in the form o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The second lamp post provided a better fit to the narrow component of the Fe K emission. Similarly, Chakraborty et al (2020) obtained an improvement in the model that fitted the observed spectrum by considering a twocomponent corona at two different temperatures. This difference in coronal temperatures could be interpreted as originating from the fact that the two components are located at different distances from the black hole.…”
Section: Discussionmentioning
confidence: 90%
“…The second lamp post provided a better fit to the narrow component of the Fe K emission. Similarly, Chakraborty et al (2020) obtained an improvement in the model that fitted the observed spectrum by considering a twocomponent corona at two different temperatures. This difference in coronal temperatures could be interpreted as originating from the fact that the two components are located at different distances from the black hole.…”
Section: Discussionmentioning
confidence: 90%